A Mathematical Study of a Two Species Eco-Epidemiological Model with Different Predation Principles - Saikh, Aktar; Gazi, Nurul Huda (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper formulates and analyzes a predator-prey model with disease in the prey. Mathematical analysis of the model system concerns the existence, uniqueness and uniform boundedness of solutions in the positive octant. The threshold condition for epidemic and the conditions for persistence are obtained. Moreover, the system is analyzed for local stability, global stability around several equilibria. Hopf-bifurcation with its nature and the stability of the bifurcating limit cycle are studied around the disease free equilibrium point. Numerical simulations are performed to justify the analytical findings. Eco-epidemilogical significance and implications of the concluded results are discussed as well.